Reconocimiento, protección y salvaguarda del paisaje cultural y patrimonio ambiental en el municipio de san Vicente del Caguán-Caquetá. (2023)
Caquetá is undoubtedly one of the many destinations to discover, which for years has remained hidden behind the shadow of the armed conflict in Colombia and in the department that for years has restricted access to many reserves and even natural national parks, then As a result of this, forests have been cut and burned for extensive livestock farming and tourists have been allowed to enter some reserves, which is generating contamination in streams, rivers and forests. All this problem leads us to propose an analysis and diagnosis. at the departmental, municipal level, locating ourselves in the rural north of the municipality of San Vicente del Caguán, conducting a survey of the reserves and tourist sites, identifying the activities and services, the shortcomings and strengths generated, to the point of generating an intervention proposal in one of the most vulnerable sites but with great tourist potential